Observational study on healthcare workers protection in the angiographic suite during the SARS-CoV-2 pandemic: before and during vax era - Massimiliano Cernigliaro; Davide Negroni; Miriana Sassone; Andrea Paladini; Alessandro Carriero; Luca Saba; Giuseppe Guzzardi (SAGE Publishing, 2021)
Background: Since the first case of Coronavirus Disease 2019 (COVID-19) in Italy, all the hospital facilities had to reform their daily activities. Amidst them, the Interventional Radiology Department in the "Azienda Ospedaliera Universitaria" of Novara (Italy) had to create a dedicated protocol for the patent's management during the pandemic. Design and Methods: The time interval between February 2020 and March 2021 was divided into three different periods and we reported the evolution of our safety protocol, the changes in our daily activities and the rates of Sars-CoV-2 infection among the healthcare workers (HCW) of the Angiographic Suite. Personnel who had positive partners/family members or who had established close contacts of another nature outside the workplace were excluded from the study, in order to reduce any bias. Results: A total of 35 HCWs served in 355 patient procedures on Sars-CoV-2 positive patients from February 2020 to March 2021. During the year there was a reduction in the morbidity rate first from 7.9% to 1.4% and then currently reaching 0%. Conclusions: Dedicated routes, elevators, establishing Filter Areas and a clear demarcation between clean and contaminated areas, Dressing and undressing procedures, Cleaning procedures and the obligation to always wear a surgical mask during the working shift are essential to prevent in-hospital infection. The vaccines' arrival seems to further reduce the risk for healthcare workers, but it is still necessary to take docile precautions in view of the new mutations of the virus.